Biofilm formation of Listeria monocytogenes isolated from fresh cheese of markets in Cercado de Lima - Villanueva, Diego (2017)
Introduction: L. monocytogenes is a bacterium of importance in public health because it causes listeriosis that has serious consequences. It is associated with the consumption of foods that can be contaminated during its production with bacteria released from pipes, surfaces and equipment biofilms. Objectives: To analyze cheese samples in order to isolate and identify L. monocytogenes and evaluate its ability to biofilm formation in two culture media. Design. Experimental, prospective study. Setting: Instituto de Investigación en Química Biológica, Microbiología y Biotecnología, Facultad de Farmacia y Bioquímica, Universidad Nacional Mayor de San Marcos, Lima, Peru. Material: 75 samples of fresh cheese from ten markets of Cercado de Lima. Methods: The microbiological analysis used methodologies of the Bacterial Analytical Manual of the Food and Drug Administration. The microplate method described by Djordjevic modified by Borucki was used to determine the ability of biofilm formation. The Kruskal-Wallis test was applied. Main outcome measures: Identification of L. monocytogenes. Results: L. monocytogenes was identified in 14 samples (18.7%), a value representing potential risk to the consumers’ health. Nine biofilm-forming strains were found and classified according to their optical density at 595 nm in weak and moderate formers, with significant differences depending on the culture medium used. The brain heart infusion (BHI) was the most effective. Conclusions: L. monocytogenes was identified in 18.7% (14/75) of samples of fresh cheese obtained in ten in Cercado de Lima’s markets. From these strains, 64.3% (9/14) were biofilm formers.